Analisis Studi Kelayakan Bisnis Konveksi Jeans di Desa Pegaden Tengah - Naelusyifa (CV. Kalimasada Group, 2023)
The convection is a business activity that is able to expand employment opportunities and provide broad economic services to the community, and can play a role directly in increasing the income and economy of the community, reducing the number existing socialization and improve the welfare of the community, especially the community Pegaden Tengah and employees who work at this convection. His study aims to analyze whether the jeans convection business is feasible to run in Pegaden Tengah. This business feasibility test will be carried out through several aspects, namely market and marketing aspects, management aspects human resources, financial aspects, and economic and social aspect. Results of the discussion of every aspect will be used as a reference to determine whether this jeans convection business worth running or not . This research using a descriptive approach and this type of research is qualitative research. The results of this study indicate that all aspects have good results and this business can run. Market and marketing aspects show that There are still many jeans enthusiasts in the city of Pegaden Tengah and the marketing techniques used can make this business known to the public. The technical aspect of this business is said to be feasible because the layout arrangement and location selection are in accordance with market segmentation.